Effect of sodium chloride as a porogen agent in mechanical properties of PLGA/HA nanocomposite scaffolds. (8th April 2021) - Mokhtarzadegan, M; Zebarjad, S Mojtaba; Bahrololoom, M E; Modarres, M
Abstract: In this study, the novel poly (lactic-co-glycolic acid)-Hydroxyapatite nanoparticles (PLGA/HA) nanocomposite scaffolds were fabricated with solvent casting and particulate leaching (SCPL) method. The role of sodium chloride (NaCl) particles with diameters of 250-400 μ m as porogen agent in the mechanical strength of the produced scaffolds was evaluated. The prepared scaffolds were characterized using Fourier transform infrared (FT-IR), X-ray diffraction (XRD), scanning electron microscopy (SEM), thermal gravimetric analysis (TGA) and compressive tests. The results showed the high compressive strength and homogenous porous structures for PLGA/HA nanocomposite scaffolds compared to pure PLGA due to the presence of HA nanoparticles in nanocomposites. Furthermore, the compressive strength of nanocomposite scaffolds increased by varying the weight ratio of hydroxyapatite nanoparticles to polymer (0, 20, 40 wt%) at constant salt ratio and decreased by increasing the weight ratio of salt particles to polymer from 1 to 3 wt% due to more porosity in nanocomposite scaffolds. These results confirmed that not only the nanocomposite scaffolds exhibited high mechanical properties, homogenous structures, as well as good porosity but also, they could be useful for bone tissue application.